STUDENTS’ MOTIVATION TOWARD THE USE OF GOOGLE CLASSROOM IN LEARNING ENGLISH DURING COVID-19 PANDEMIC AT SMA N 1 SUKOHARJO - Rosita Ambarwati; Berlinda Mandasari (Journal of Arts and Education, 2021)
Motivation is one of the essential parts of the learning process. Motivation can be interpreted as the students’ desire to learn something because the higher motivation, the better students will be. The purpose of this study is to explore the level of student motivation toward the use of Google classroom in learning English during the Covid-19 pandemic at SMA N 1 Sukoharjo in the academic year 2020/2021. This study also finds out the dominant type, whether intrinsic or extrinsic motivation. This study uses descriptive qualitative, and the technique uses for collecting the data are questionnaires and interviews. The data were presented by using percentage, frequency, mean score, and standard deviation (S.D). The finding of this study showed that the mean score of intrinsic motivation (3.60) was higher than extrinsic motivation (3.43). The mean score of overall motivation is 3.51 was considered a moderate level of motivation. However, the majority of students learn English best because of their intrinsic motivation. Students are interested in learning English and love to take English classes. Students can do the assignments given by the teacher and want to master the English material taught by the teacher. To master English, students have to study hard and practice it in their daily life. So, teachers must be able to provide various teaching strategies to cope with both intrinsically motivated students and extrinsically motivated ones.